The impact of growth mindset training on entrepreneurial action among necessity entrepreneurs: Evidence from a randomized control trial - Morris, Shad; Carlos, Chad; Kistruck, Geoffrey M.; Lount, Robert B.; Thomas, Tumsifu Elly (Strategic Entrepreneurship Journal, 2023)
Abstract Research Summary Although entrepreneurship training programs are designed to help necessity entrepreneurs acquire skills and capabilities to take entrepreneurial action, participants in these programs often fail to do so. In partnership with a local government agency, we conducted a randomized field experiment involving 165 entrepreneurs in rural Tanzania where in addition to providing technical‐skills training, approximately half of the participants also received “growth mindset” psychological training. Those who received the growth mindset training displayed more entrepreneurial action in their business than those in the control group. Importantly, higher levels of entrepreneurial self‐efficacy mediated the positive impact on entrepreneurial action displayed by participants who received the growth mindset training. We discuss how complementing traditional technical‐based training with growth mindset training can improve the efficacy of entrepreneurship training programs. Managerial Summary Entrepreneurship training programs often fall short in translating knowledge into action. To address this issue, we conducted an experiment with 165 entrepreneurs in rural Tanzania. All participants received technical‐skills training, but half were also exposed to “growth mindset” training. Those who received the growth mindset training displayed greater initiative in business growth. The newfound confidence and grit they gained empowered them to apply learned principles effectively, ultimately enhancing the effectiveness of entrepreneurship training programs.